(untitled) (Indonesian Sports Justice Review, 2024)
Sports in Indonesia hold significant potential to foster social justice, national unity, and reconciliation among the country’s diverse ethnic, religious, and social groups. This paper examines the role of sports as a tool for promoting inclusivity and unity in post-conflict Indonesia, particularly in bridging divides between urban and rural populations, and between different ethnic and religious communities. Through an analysis of government-sponsored sports initiatives, grassroots programs, and major sporting events, the study explores how sports can act as a vehicle for social change by promoting values such as fairness, teamwork, and mutual respect. Case studies of successful national and regional sporting events, such as the PON (Pekan Olahraga Nasional) and community-level sports programs, illustrate the potential of sports to address social inequalities and bring diverse groups together. The paper concludes with recommendations on how to leverage sports for broader social justice goals, including the integration of sports programs into national policies on peacebuilding, education, and cultural exchange.